PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN DAUN JARAK SEBAGAI BAHAN BAKU PEREKAT PESTISIDA ORGANIK DI DESA KLOMPANGAN KECAMATAN AJUNG KABUPATEN JEMBER JAWA TIMUR - Andriani, Devin Dwi; Musyafa, Muhammad Zainal Ali; Sasmitaningtyas, Maulidya Tri; Sulistyowati, Jeni; Wardana, Elizia Flauren; Wahyuningsih, Sri; Subekti, Sri (PAPUMA: Journal of Community Services, 2025)
Community service activities in Klompangan Village, Ajung District, Jember Regency, aim to empower farmers to overcome the obstacles of using chemical pesticides which are expensive and have a negative impact on the environment. This activity is motivated by problems in controlling plant pests which require effective, environmentally friendly and economical solutions. Farmers, especially small farmers, face difficulties in obtaining or purchasing chemical pesticide adhesives due to high prices and limited distribution. This program is designed to increase public awareness, especially farmers, about the importance of protecting the environment and reducing the negative impact of the use of synthetic pesticides on health and the environment. The training was carried out through lecture and demonstration methods, which provided participants with an understanding of environmentally friendly biological control techniques for Plant Pest Organisms (OPT), how to make organic pesticide adhesive from natural ingredients such as castor leaves, hibiscus leaves and cooking oil, as well as their benefits for agriculture. sustainable. The process for making organic adhesive is designed to be simple so that farmers can produce it independently. The active participation and high enthusiasm of the participants showed great interest in environmentally friendly agricultural solutions, while emphasizing the importance of community-based training to improve community skills and motivation. It is hoped that the results of this activity will empower farmer groups to produce and use organic pesticide adhesives independently, disseminate knowledge to fellow members, and support more sustainable agricultural practices for the welfare of the community